Predicting poor outcome Crohn's disease at the time of first diagnosis - Watermeyer, Gillian (Department of Public Health and Family Medicine, 2014)
Over time, the majority of patients with Crohn's disease (CD) will develop irreversible gastrointestinal (GIT) damage, notably strictures or fistulas, impacting negatively on quality of life and resulting in hospitilisation and surgery. Early and aggressive drug therapy with immunomodulators (IMMs) and biologics may alter the likelihood of these complications and improve long-term outcomes. However, this approach is extremely expensive and carries its own battery of side-effects such as infections and malignancy. In addition there are a sizable number of patients with CD who will have a benign disease course and never require potent medical therapies or surgical intervention. As a result, there has recently been a surge of interest in early identification of those people who are at risk of developing complicated disease. The aim of our study was thus to indentify predictive factors for poor outcome CD in a South African setting, in order to select those who would most benefit from early and aggressive medical therapies.